EFEKTIVITAS DISTRAKSI VIDEO GAME TERHADAP PENURUNAN KECEMASAN ANAK USIA 7-10 TAHUN PADA TINDAKAN ANESTESI INFILTRASI - Rini Triani Sjamsul; Witriana Latifa Wibisono; Ika Anisyah Lubis; Roosje Rosita Oewen (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: Children’s anxiety toward dental care in the clinic creates significant problems for the patient and the dental professionals. One of the techniques to overcome the anxiety of the patient is by using video game distraction. This study purpose to determined the effectiveness of video game distraction on reducing the level of anxiety in children between 7-10 years during infiltration anesthesia. Method: A pre-test post-test quasi-experimental study was conducted involving 32 purposive sampling subjects; divided into two groups (16 with video game distraction and 16 as a control). Facial Image Scale (FIS) was used to assess anxiety. Result: Independent t-test showed that there were significant differences between the two groups (p<0,05) with a decrease in the level of anxiety in the group with video game distraction by 47,40% while there was an increase of 72,40% in the control group. Conclusion: Video game distraction could be effective in reducing anxiety in children aged 7-10 years under infiltration anesthesia with a reduction rate of 47,40%.